Late treatment of mandible fracture after third molar removal (Research, Society and Development, 2022)
Surgical management of impacted third molars is a treatment performed by dentists and its indicated for various conditions, among the indications has the prevention of mandibular fracture, but this is a factor that has been discussed and is controversial. Fractures caused by a third molar can occur, and on the other hand, the fractures after or during the management of impacted third molar are a possible complication. Surgical planning as the indication to the surgery has to be performed to avoid complications as the fracture. Thus this study aims to report a case about a mandible fracture after third molar extraction, presenting edema, pain, and restriction in mandible mobility in 01-day follow-up. A 27-year-old female was referred to the oral and maxillofacial surgery service of the Santa Casa Hospital of Araçatuba (Araçatuba, Brazil), reporting dental history of third molar removal, with immediately chief complaints. In the assessment, the patient presented edema, pain, malocclusion, and restriction in mandible mobility, and the panoramic X-ray showed a mandible fracture with displacement. The patient underwent surgery under general anesthesia to open reduction with internal fixation (ORIF) through an intraoral approach. On the follow-up, the patient showed an improvement in mouth opening and mandibular mobility without pain or infection signs. The panoramic X-Rays showed us the bone fracture healing.